CYCLOPS IN LARGE WHITE YORKSHIRE PIGS - KARTHICKEYAN, S M K; RAMESH, J; GOPINATHAN, A; SIVASELVAM, S N (The Indian Journal of Animal Reproduction, 2011)
A peculiar condition called Cyclops was observed in two different Large White Yorkshire piglets, which hadvarying features and there was no involvement of boar since they were from different sire groups.
Keywords: Cyclops; Large White Yorkshire; pigs; India